HIF-1α-mediated upregulation of SERCA2b: The endogenous mechanism for alleviating the ischemia-induced intracellular Ca2+ store dysfunction in CA1 and CA3 hippocampal neurons. Issue 5 (May 2016) - Kopach, Olga; Maistrenko, Anastasiia; Lushnikova, Iryna; Belan, Pavel; Skibo, Galina; Voitenko, Nana
Graphical abstract: Highlights: OGD impairs intracellular Ca 2+ regulation and Ca 2+ store function in CA1 neurons. Ischemic impairments were accompanied by downregulated PMCA1 and PMCA2 mRNAs. In CA3 neurons, OGD increased SERCA2b mRNA with no effects on Ca 2+ regulation. Stabilization of HIF-1α upregulated the SERCA2b mRNA in CA1 neurons. HIF-1α stabilization improved Ca 2+ regulation and Ca 2+ stores in CA1 neurons post-OGD. Abstract: Pyramidal neurons of the hippocampus possess differential susceptibility to the ischemia-induced damage with the highest vulnerability of CA1 and the lower sensitivity of CA3 neurons. This damage is triggered by Ca 2+ -dependent excitotoxicity and can result in a delayed cell death that might be potentially suspended through activation of endogenous neuroprotection with the hypoxia-inducible transcription factors (HIF). However, the molecular mechanisms of this neuroprotection remain poorly understood. Here we show that prolonged (30 min) oxygen and glucose deprivation (OGD) in situ impairs intracellular Ca 2+ regulation in CA1 rather than in CA3 neurons with the differently altered expression of genes coding Ca 2+ -ATPases: the mRNA level of plasmalemmal Ca 2+ -ATPases (PMCA1 and PMCA2 subtypes) was downregulated in CA1 neurons, whereas the mRNA level of the endoplasmic reticulum Ca 2+ -ATPases (SERCA2b subtype) was increased in CA3 neurons at 4 h of re-oxygenation after prolonged OGD. These demonstrate distinct susceptibility of CA1 and CA3 neurons to the ischemic impairments in intracellular Ca 2+ regulation and Ca 2+ -ATPase expression. Stabilization of HIF-1α by inhibiting HIF-1α hydroxylation prevented the ischemic decrease in both PMCA1 and PMCA2 mRNAs in CA1 neurons, upregulated the SERCA2b mRNA level and eliminated the OGD-induced Ca 2+ store dysfunction in these neurons. Cumulatively, these findings reveal the previously unknown HIF-1α-driven upregulation of Ca 2+ -ATPases as a mechanism opposing the ischemic impairments in intracellular Ca 2+ regulation in hippocampal neurons. The ability of HIF-1α to modulate expression of genes coding Ca 2+ -ATPases suggests SERCA2b as a novel target for HIF-1 and may provide potential implications for HIF-1α-stabilizing strategy in activating endogenous neuroprotection.